EFEKTIVITAS PEMBELAJARAN BERBASIS BUDAYA LOKAL TERHADAP KARAKTER SISWA SEKOLAH DASAR - Widowati, Ayu Saly; Fara Zaitun Chusnullita; Eko Handoyo; Indriana Eko Armaidi; Muh Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of implementing local wisdom-based learning in strengthening students’ character at the elementary school level. Amid the massive wave of globalization, the erosion of moral values and the loss of cultural identity have become serious challenges in the world of education. Local wisdom-based learning serves as an instructional strategy that integrates traditional values, norms, and local customs into the school curriculum to shape students’ personalities rooted in the nation’s culture. The research method employed is descriptive quantitative, involving elementary school students as research subjects. Data collection instruments include character observation questionnaires, interviews, and documentation. Data analysis was conducted to compare students’ character traits before and after the implementation of teaching materials incorporating local wisdom. The results of the study indicate that local culture-based learning is significantly effective in improving students’ character, particularly in terms of religiosity, cooperation, honesty, and discipline. Through the internalization of local values relevant to daily life, students find it easier to understand and practice social ethics compared to relying solely on theoretical approaches. This contextual learning process not only enhances cognitive understanding of local culture but also fosters a sense of pride and love for the homeland. The conclusion of this study affirms that the integration of local wisdom into the elementary education ecosystem is a vital instrument in realizing the Pancasila Student Profile—students with strong character and a global perspective who do not lose their local identity.